Neurocriminologia, fatores biopsicossociais e justiça criminal: impasses e mudanças - Esteves, Andressa Barbosa (2022)
Based on the assumption of the complexity of the phenomenon of crime and violence, this research aims to analyze the emergence and development of Neurocriminology as a science that studies human behavio r and criminal conduct in depth. Thus, this Dissertation aims to outline the main aspects involving Neurocriminology, Criminology and the Brazilian Criminal Justice System. It is understood that, due to the great technological advances in the last decades, the Neurosciences gained greater scientific support. His discoveries reignited debates that go back to the beginning. The existence or not of free will and how it affects criminal accountability is the subject of much controversy among scientists, jurists and philosophers. Despite the experiments that revealed the precocious decision making by the unconscious, such a discovery is still not able to reap what is understood about criminal responsibility. Biopsychosocial factors, however, pointed out by neuros cientists in their research, bring a new view on degrees of culpability, which allows a more humanized look at the agent who commits a crime, insofar as it is possible to understand which factors exert an influence on behavior violent. This understanding i s necessary to open doors for changes in the way in which punishment and punishment is demanded in society, insofar as studying criminal behavior will give rise to a more humanized look at the figure of the offender, which consequently may lead to more eff ective penalties, away from the retributivism that guides the Brazilian Criminal Justice System. The object of this study is addressed through bibliographical , legislation and jurisprudencial research, with the aim of outlining a complete overview of the e volution and importance of neurocriminology. The need for transformation of the Brazilian Criminal System in view of the vertiginous rates of violence, the neurocriminological questions and teachings validate the relevance of this research.